Conceptual Design of a Generic Nodal Abstraction (GNA) for a Human-Agent Collaboration Systems - Abbas Mohammed K.; Abdul Majid M.; Sharifuddin Ahmad M. (Institute of Physics Publishing, 2023)
Abstracting; Conceptual design; Green computing; Multi agent systems; Simulation platform; Collaborative systems; Critical challenges; Distributed data; Generic approach; Modeling and simulation platforms; Modelling softwares; Organizational process; Workflow process; Software agents